Pengolahan Limbah Cair Rumah Potong Ayam Menggunakan Sistem Filtrasi dan Ozon Dalam Menurunkan Nilai BOD, COD, dan TSS - Donny Yuslan Cortheo; Agus Budianto (Universitas Riau, 2024)
Processing of wastewater in chicken slaughterhouses is a must in the framework of environmental preservation. Currently, there are many water outputs resulting from wastewater treatment in chicken slaughterhouses that still do not meet the quality standards for wastewater treatment set by the government. Problems in the wastewater treatment plant are mainly caused by the design and capacity of the incoming waste to the wastewater treatment plant which exceeds the initial design. The use of Filtration and Ozone technology is used to reduce the values of BOD, COD, and TSS in wastewater. This study aims to look at the values of BOD, COD, and TSS and their effectiveness with the use of Filtration systems and a combination of Filtration systems and Ozone systems. The research method uses physical and chemical methods, namely the filtration system which is expected to reduce the TSS value and also react wastewater after filtration with ozone mixed water to reduce BOD and COD values. The results of this study showed that the BOD value decreased by 97.14%, the COD value decreased by 64.27%, while the TSS value decreased by 97.14%.